2008
DOI: 10.1111/j.1753-4887.2007.tb00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic and Prebiotic Influence Beyond the Intestinal Tract

Abstract: Probiotics and prebiotics have long been appreciated for their positive influences on gut health. Research on the mechanisms and effects of these agents shows that their impact reaches beyond the intestine. Effects on the microecology and pathology of the oral cavity, stomach, and vaginal tract have been observed. Likely mediated through immune influences, systemic effects such as reduced severity of colds or other respiratory conditions, impact on allergy incidence and symptoms, and reduced absences from work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(63 citation statements)
references
References 135 publications
2
60
0
1
Order By: Relevance
“…Enhancement of humoral and cellular immunity following administration of probiotics has been noted in various animal [72,73] and human studies [74][75][76][77]. This has been particularly shown for RTIs [5][6][7]24,[26][27][28][29]78]. Notably, two of the RCTs included in this review reported an appreciable increase in the total numbers of CD4 + and CD8 + T-lymphocytes in the probiotic-treated group compared with the placebo group [36,39].…”
Section: Referencementioning
confidence: 77%
“…Enhancement of humoral and cellular immunity following administration of probiotics has been noted in various animal [72,73] and human studies [74][75][76][77]. This has been particularly shown for RTIs [5][6][7]24,[26][27][28][29]78]. Notably, two of the RCTs included in this review reported an appreciable increase in the total numbers of CD4 + and CD8 + T-lymphocytes in the probiotic-treated group compared with the placebo group [36,39].…”
Section: Referencementioning
confidence: 77%
“…Probiotic agents possess the properties of non-pathogenic, non-toxic, resistance to gastric acid, adherence to gut epithelial tissues producing antibacterial substances (Suvarna and Boby 2005). There are evidences that administration of probiotics decreases the risk of systemic conditions, such as allergy, asthma, cancer and several other infections of the ear, urinary tract (Lenoir-Wijnkoop et al 2007). …”
Section: Probioticsmentioning
confidence: 98%
“…However, these bacteria are not the only causative agents perhaps just markers of a pathogenic biofilm [42,43]. Focusing on the genesis of the unhealthy oral biofilm will enable the practitioner to prevent or treat a host of oral pathologies and related systemic disorders [33,34]. The patient's oral hygiene practices should be thoroughly reviewed, full and complete oral prophylaxis performed and Cervetic Plus TM (Ivoclar) varnish applied to reduce the level of the oral pathogens [2,19,57].…”
Section: Introductionmentioning
confidence: 98%
“…The introduction of probiotics into dentistry means that the profession should now consider the entire biofilm complex instead of just the pathogen-specific model of plaque [33]. Previous considerations were to mainly focus on the specific ''pathogens'', such as ''mutans streptococci'' and the genus ''Lactobacillus'' [62].…”
Section: Introductionmentioning
confidence: 99%